Larangan Perayaan Tahun Baru Masehi Di Kota Banda Aceh: Regulasi, Implementasi, Dan Respon Masyarakat - Inayat, Muhammad; Fauzi, Ahmad (Mahad Aly Al Fithrah, 2025)
This research aims to explore the prohibition of the celebration of the Gregorian New Year in Banda Aceh through an analysis of the regulations enacted, the implementation of policies in the field, and the community's response to these policies. Aceh is an area that implements Islamic law, so Banda Aceh has special regulations that prohibit various activities that are considered incompatible with Islamic values, including the celebration of the Gregorian New Year. This research uses a qualitative approach with a case study method. The focus of the research includes regulations, implementation, and community responses to the policy. Data were collected through interviews, observation, and documentation. In addition, document analysis of qanun, circulars, and media coverage was conducted to complement primary data. The results of the study show that the ban on New Year celebrations in Banda Aceh has succeeded in upholding Islamic values but has not been optimal in maintaining social cohesion among religious communities. This policy has created tension between the enforcement of religious identity and the protection of diversity. The study recommends a more inclusive and dialogical approach to minimize social distance, as well as the need for further research to measure the long-term impact of this policy on multicultural societies.